Odpowiedź:
Wyjaśnienie:
C₂H₅OH + 3O₂ → 2CO₂ + 3H₂0
mC₂H₅OH = 2 * 12u + 1 * 16u + 6* 1u = 24u + 16u + 6u = 46u
%C w C₂H₅OH = [tex]\frac{24u}{46u}[/tex] * 100% = 52,17%
2C₂H₄(OH)₂ + 5O₂ → 4CO₂ + 6H₂O
mC₂H₄(OH)₂ = 2 * 12u + 2 * 16u + 6 * 1u = 24u + 32u + 6u = 62u
%C w C₂H₄(OH)₂ = [tex]\frac{24u}{62u}[/tex] * 100% = 38,71%
C₁₅H₃₁COOH + 23O₂ → 16CO₂ + 16H₂O
C₁₅H₃₁COOH + 15O₂ → 16CO + 16H₂O
C₁₅H₃₁COOH + 7O₂ → 16C + 16H₂O
mC₁₅H₃₁COOH = 16 * 12u + 2 * 16u + 32 * 1u = 192u + 32u + 32u = 256u
%C w C₁₅H₃₁COOH = [tex]\frac{192u}{256u}[/tex] * 100% = 75%